Maternal and paternal age at delivery, birth order, and risk of childhood onset type 1 diabetes: population based cohort study - Stene, Lars C (BMJ, 2001)
OBJECTIVE: To estimate the associations of maternal and paternal age at delivery and of birth order with the risk of childhood onset type 1 diabetes. DESIGN: Cohort study by record linkage of the medical birth registry and the national childhood diabetes registry in Norway. SETTING: Norway. SUBJECTS: All live births in Norway between 1974 and 1998 (1.4 million people) were followed for a maximum of 15 years, contributing 8.2 million person years of observation during 1989-98. 1824 cases of type 1 diabetes diagnosed between 1989 and 1998 were identified. MAIN OUTCOME MEASURES: Incidence of type 1 diabetes. RESULTS: There was no association between maternal age at delivery and type 1 diabetes among firstborn children, but among fourthborn children there was a 43.2% increase in incidence of diabetes for each five year increase in maternal age (95% confidence interval 6.4% to 92.6%). Each increase in birth order was associated with a 17.9% reduction in incidence (3.2% to 30.4%) when maternal age was 20-24 years, but the association was weaker when maternal age was 30 years or more. Paternal age was not associated with type 1 diabetes after maternal age was adjusted for. CONCLUSIONS: Intrauterine factors and early life environment may influence the risk of type 1 diabetes. The relation of maternal age and birth order to risk of type 1 diabetes is complex.